Machiavellian, Equity Sensitivity, and Law Enforcement on the Perception of Tax Evasion Ethics - Dian Sulistyorini Wulandari; Edi Tri Wibowo; Perdana Ricardo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of Machiavellian, Equity Sensitivity, and Law Enforcement on the Ethical Perception of Tax Evasion with a case study at KPP Pratama Cibitung. This research uses a quantitative approach. The analysis used is Multiple Linear Regression Analysis with t-test, f-test, and coefficient of determination. The test instrument used in this study was SPSS Version 25. The test results in this study were the Machiavellian variable had a positive and significant effect on perceptions of tax evasion ethics, while equity sensitivity and law enforcement variables had a negative and significant effect on perceptions of tax evasion ethics. The coefficient of determination is 0.309 or 30.9%, which means that the magnitude of the influence of Machiavellian, equity sensitivity, and law enforcement on the ethical perception of tax evasion is 30.9% and the remaining 69.1% is explained by other factors. which were not described and tested in this study.